2016
DOI: 10.3920/jiff2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Habitats and nutritional composition of selected edible insects in Zimbabwe

Abstract: Edible insects are gaining recognition as food with potential of contributing to attainment of household food security. In sub-Saharan Africa, sustainable use of insects as food is threatened by lack of data on host plants and habitatassociations. In addition, lack of nutritional data on most edible insects reduces consumer confidence and limits integration of insect consumption with other food sources. This study was undertaken to review, collate and assembledispersed information of some edible insects of Zim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 10 publications
4
28
1
Order By: Relevance
“…1 Framework for the design of the questionnaire on possible factors that can influence insect consumption patterns different types of insects. The results are in line with previous research, which observed that entomophagy is a common practice in Zimbabwe (DeFoliart 1997;Dube et al 2013;Musundire et al 2016). The data on consumption frequencies shows that a significantly higher percentage (63.9%) of the rural respondents consumed edible insects more than three times a week on average when it is insect harvest season compared with urban respondents (14.5%) (χ 2 = 101.766, df-= 3, p < 0.001).…”
Section: Insect Consumption Patternssupporting
confidence: 90%
See 1 more Smart Citation
“…1 Framework for the design of the questionnaire on possible factors that can influence insect consumption patterns different types of insects. The results are in line with previous research, which observed that entomophagy is a common practice in Zimbabwe (DeFoliart 1997;Dube et al 2013;Musundire et al 2016). The data on consumption frequencies shows that a significantly higher percentage (63.9%) of the rural respondents consumed edible insects more than three times a week on average when it is insect harvest season compared with urban respondents (14.5%) (χ 2 = 101.766, df-= 3, p < 0.001).…”
Section: Insect Consumption Patternssupporting
confidence: 90%
“…For this purpose, a case study was made in Zimbabwe. Although mopane worms and termites are the most popularly consumed edible insects in Zimbabwe (Gardiner and Gardiner 2003;Onigbinde and Adamolekun 1998), Eulepida species (Dube et al 2013;Musundire et al 2016;Onigbinde and Adamolekun 1998) and Henicus whellani (Musundire et al 2014a, b) are also commonly consumed in some regions of the country. The current study, next to overall insect consumption, focused on Eulepida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis (calculated on dry matter basis) indicated that crude protein was high in the three edible insects, 71.2% in L. migratoria, 57% in I. belina and 31.3 in E. delegorguei ( Table 3). The protein content of insects studied was observed to vary widely but results were similar to published data for various edible insects in Zimbabwe and elsewhere especially for I. belina [3,4,19]. In other studies, authors have reported varying protein content from our results for Imbrasia belina [20].…”
Section: Resultssupporting
confidence: 88%
“…Generally, insects that are mostly consumed are those that can be gathered in large numbers and meet organoleptic preferences of consumers [3]. In Zimbabwe, entomophagy has been reported as a common practice in both rural and urban areas in the country's 10provinces [4]. A significant number of insect types are consumed by the Zimbabwean population, and in other areas some insects are sold for money or bartered for other necessities [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation